FARMING SYSTEMS IN TWO LESS FAVOURED AREAS IN PORTUGAL: THEIR DEVELOPMENT FROM 1989 TO 2009 AND THE IMPLICATIONS FOR SUSTAINABLE LAND MANAGEMENT. (8th November 2013) - Jones, Nádia; de, Jan; Duarte, Filomena; Rodrigo, Isabel; Poortinga, Ate; Fleskens, Luuk; Stringer, Lindsay C.
ABSTRACT Since the late 1980s, sustainable land management is one of the objectives of the European Commission in Less Favoured Areas. In this paper, we investigate the economic and environmental sustainability of farming systems in two less favoured areas in Centro and Alentejo areas of Portugal. The specific objectives were the following: (i) to characterise the farming systems; (ii) to analyse their development over a 20‐year period (1989–2009); and (iii) to investigate to what extent these farming systems contribute to sustainable land management. The diversity of the farming systems was identified through a survey and cluster analysis and compared with the Farm Accountancy Data Network classification on types of farming. Indicators on the economic and environmental sustainability were estimated, namely, farm net income, return to labour and rotation management, on the basis of a survey, Farm Accountancy Data Network database and Landsat imagery, respectively. Results indicate an increased focus on livestock in the past 20 years (1989–2009). In Centro, rotation management was not affected. The small ruminant farms have been able to retain a positive farm net income but that was only possible with a below average return to labour. In Alentejo, the increased focus on livestock, cattle in particular, led to an intensification of fodder production on certain plots. Mixed crop–livestock farms show a negative farm net income since 1995 and depend heavily on subsidies to remain viable. As other studies in southern Europe have shown, farm strategies have often been directed towards lowering labour inputs, lowering forage deficits through on‐farm produced resources and acquiring subsidies. Copyright © 2013 John Wiley & Sons, Ltd.